Thromboembolic Risk among Patients on Dual Antiplatelet Therapy with or without Heparin Thromboprophylaxis - Gmeiner, Jonas; Kaiser, Rainer; Fischer, Julius; Krächan, Angelina; Wasner, Lisa; Marchant Seiter, Thomas; Weckbach, Ludwig; Stark, Konstantin; Hausleiter, Jörg; Massberg, Steffen; Scherer, Clemens (Thrombosis and Haemostasis, 2025)
Venous thromboembolism (VTE) is a common complication among hospitalized patients. Low-molecular-weight heparin (LMWH) is recommended for thromboprophylaxis, but its benefits in non-surgical patients, particularly those receiving dual antiplatelet therapy (DAPT), remain unclear. Currently, evidence on the risks and benefits of LMWH thromboprophylaxis in patients on DAPT is lacking.This retrospective cohort study included patients hospitalized in the cardiology departments of two hospitals of LMU University Munich between May 2015 and April 2025. Patients receiving DAPT, defined as treatment with aspirin and a P2Y12 inhibitor, were analyzed. The study population was divided into two groups: those who received LMWH prophylaxis and those who did not. The primary endpoint was the incidence of VTE during hospitalization, confirmed through imaging techniques. Secondary endpoints included the need for erythrocyte transfusion.A total of 8,619 patients receiving DAPT were included, of which 2,378 were receiving LMWH prophylaxis. The incidence of VTE was very low and did not differ between the LMWH and non-LMWH groups (0.04% versus 0%, p = 0.28). Subgroup analysis revealed higher bleeding rates as mirrored by more erythrocyte transfusions in the LMWH group (9.4 versus 5.1%, p = 0.004).In patients receiving DAPT, LMWH thromboprophylaxis was associated with a comparably low incidence of VTE but a higher rate of erythrocyte transfusions in subgroup analysis.
Keywords: venous thromboembolism; dual antiplatelet therapy; heparin; low molecular weight